FORMATION AND IMPROVEMENT OF LOCAL BUDGET REVENUES - Rustamov , Maksud Suvankulovich; Egamberganov , Mirzabek Odilbek ugli (Educational Research in Universal Sciences, 2024)
In this article, the study of methods of development of budget revenues through the formation and improvement of local budget revenues is presented. The importance of the formation and improvement of local budget revenues was highlighted, as well as suggestions and recommendations were developed regarding the formation of local budget revenues and their analysis.